Implementasi Program CSR PT.Timah (Persero) Tbk Terhadap Masyarakat Tani Desa Gemuruh Kecamatan Kundur Barat Kabupaten Karimun - RIA ANGGRAINI; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This PT.TIMAH Kundur represent the assistant executor running aid CSR centering from PT.TIMAH residing in Bangka. All aid raised by society which have place to around mining. this PT.TIMAH Kundur pursuant to existing program have to be raised to board of directors of PT.TIMAH Bangka, full located decision at holdingnya. Accepted or don’t it him aid application of pursuant to survey conducted by board of directors. As for intention of this is research: To know the forms program in the CSR PT.TIMAH Thundering Countryside, To know whether execution program the CSR can be felt by Prosperous Source Farmer Group. This Research in determination sampel by using Technique of Simpel Random conducted by taking chosen people who by researcher to be made by sampel. Based for such criterion is Prosperous Source Farmer Group residing in Thundering Countryside [of] Subdistrict of Kundur of West of Regency Karimun. Way of this intake sampel is Prosperous Source Farmer Group amounting to 100 people and taken as sampel of equal to 50% that is as much 50 farmer people..Form the implementation program the CSR of a lot of happened by the social change of society economics. Change that at happened Prosperous Source Farmer Group referred as with the social change. The by change happened caused by its is aid from program of CSR PT.TIMAH ( persero) Tbk. As for social change of Thundering Countryside society economics specially Prosperous Source Farmer group like pattern eat the, house form, clothes, used motor vehicle, furniture of used communication means and houseKeyword : Implementation, Program The CSR PT.TIMAH, Farmer Society